GC-MS PROFILING OF ETHANOLIC EXTRACT OF MORINGA OLEIFERA LEAF - AYON BHATTACHARYA,; GOUTAM GHOSH,; DIVYA AGRAWAL,; PRATAP KUMAR SAHU,; SANJAY KUMAR,; SUDHANSHU SEKHAR MISHRA, (International Journal of Pharma and Bio Sciences, 2014)
To analyze and characterize the phytochemical compounds of ethanolic leaf extract oforinga oleifera using GC-MS. The phytochemical screening of ethanolic extract was carried out according to standard procedures stated by WHO guidelines. The various bioactive compounds of the extract weredentified by GC-MS technique.The results of the GCMS analysis revealed 35 compounds in the ethanolic extract of oringa oleifera leaves. Among the 35 compounds the following 15 major compounds revealed iththe maximum peak percentage area in parenthesis shown in table 1 : 1,2,3-Cyclopentanetriol 1.63), L-Galactose, 6- eoxy (4.35), n-Hexadecanoic acid (28.84), Tetradecanoic acid (2.12), cis- accenic acid (26.45), Octadecanoic acid (4.91), Palmitoyl chloride (1.56), 3-Chloro-N- sochroman-1-ylmethyl-propionamide (5.61), 2-Butenoic acid, 2-methoxy-3-methyl-, methyl ester 1.77) , 3,4- ichlorobenzonitrile (2.21), Mannitol,1,4-di-O-methyl-, tetraacetate (1.09), beta.-l- amnofuranoside, 5-O-acetyl-thio-octyl (1.01), Vitamin E(2.07), gamma.-Sitosterol (2.23), Pregn- ,7-diene-3-ol-20-one (1.47). Their respective retention times being as. follows: 13.03,15.28,18.62,18.67,20.35,20.52,21.62,23.36,23.46,23.67,23.90,23.94,27.85,29.16 29.26. The minor compounds are 4,5-Diamino-2- ydroxypyrimidine (0.45), 4H-Pyran-4-one,2,3-dihydro-3,5-dihydroxy-6-methyl (0.93), enzofuran,2,3-dihydro (0.64), Benzeneacetonitrile,4-hydroxy (0.64), 2- Cyclohexenone,4-cetamido(0.68),4-((1E)-3-Hydroxy-1-propenyl)- - ethoxyphenol(0.39), Cyclopropaneoctanal,2- ctyl (0.23), 5-Eicosene, (E) (0.54), Octadec-9-enoic acid (0.74), 5-Eicosene, (E) (0.54), Oxirane, tetradecyl (0.64), trans-13-Octadecenoic acid (0.41), 6- ctadecenoic acid, (Z) (0.28), cis-9- exadecenal (0.21), Cyclopentadecanone,2-hydroxy (0.25), Cyclopropaneoctanal,2-octyl (0.26), leic Acid (0.35), Oleylalcohol, heptafluorobutyrate (0.90),7- entadecyne (0.70),trans-13- ctadecenoic acid (0.60).The ethanolic leaf extract of Moringa oleifera proved to be a reservoir of bioactive compounds identified by GC-MS which could prove effective in the treatment of various diseases.